Tunable Metasurfaces: The Path to Fully Active Nanophotonics - Badloe, Trevon; Lee, Jihae; Seong, Junhwa; Rho, Junsuk (Advanced photonics research, 2021)
In the field of nanophotonics, metasurfaces have come to the forefront in real‐world applications, owing to their accessible exotic optical properties that can be readily designed and fabricated using currently available techniques. The subwavelength dimensions and lightweight characteristics of metasurfaces are attractive qualities for the miniaturization of optical devices and are already exploited in devices that can rival, and sometimes even outperform, conventional bulky optics. Over the past decade, ample research has been undertaken to produce high‐performance metasurfaces with exciting optical properties that cannot be found in nature or achieved with conventional optics. To open the path to widely used devices in our everyday lives, the next obvious step for metasurfaces is the development of tunability. Herein, the techniques and development of applications of tunable metasurfaces are presented through the incorporation of active materials and controllable external stimuli, and the uncovered tunable characteristics are critically analyzed. The review rounds up by proposing the future directions and prospects for actively tunable metasurfaces and their potential practical applications. The recent progress of metasurfaces from static to fully tunable at the meta‐atom level is reviewed, focusing on experimentally realized applications in the visible and IR regime. The different methods of tuning metasurfaces are discussed in terms of switchable, continuously tunable, and fully reprogrammable devices. The review rounds up with comments on the future directions of the field.